DEVELOPMENT OF DIGITAL BOOK-BASED TEACHING MATERIALS TO ENHANCE THE EFFECTIVENESS OF SCIENCE LEARNING FOR FOURTH GRADE AT MIT BERKAH (PIONIR: JURNAL PENDIDIKAN, 2025)
This research aims to develop digital book-based teaching materials to increase the effectiveness of Natural Sciences (IPAS) learning in elementary schools. With the development of information technology, the use of digital books as a learning resource can provide a more interactive, interesting and easily accessible learning experience for students. The research method used was research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The first stage begins with a needs analysis, followed by designing and developing digital books that are adapted to the applicable curriculum. Furthermore, the digital book was tested on a number of students to determine the extent to which this book could increase students' understanding and involvement in science learning. The results show that digital book-based teaching materials increase students' learning motivation, understanding of the material, and practical skills in science subjects. Therefore, the development of digital book-based teaching materials is highly recommended as an alternative to improving the quality of learning, which ismore effective and enjoyable.Keywords: ADDIE Model, Digital book- based Teaching Materials, Educational Technology, Natural sciences.